Clinical experience of chinese herbal medicine ameliorates dermatologic events from epidermal growth factor receptor inhibitors for lung cancer: A case series - Hung, Yu-Chiang; Chin, Chieh-Ying; Lee, Yi-Chiao; Chen, Yen-Hao; Tsai, Ming-Yen (Explore (New York, N.Y.), 2019)
To summarize the clinical efficacy and safety of Chinese herbal medicine (CHM) in the treatment of dermatologic events resulting from epidermal growth factor receptor (EGFR) inhibitors according to our experience of ten patients. Four males and six females, 35–73 years old, mainly with acneiform rash associated with EGFR inhibitors on the face, scalp, perineum, four limbs, and upper trunk, were treated at our traditional Chinese medicine (TCM) clinic in 2016 and 2017. CHM was prescribed thrice daily for 3.4 weeks, with clinical evaluation and photographic documentation performed during treatment. Size, severity, and quality of life (QoL) were documented. Therapeutic response was evaluated using the Skindex-16 dermatologic questionnaire and body surface area (BSA). Our retrospective case series demonstrated significant improvement in QoL in 10 subjects with EGFR inhibitor-related skin toxicity treated with CHM. Mean overall scores of the Skindex-16 survey fell from 74.5% at baseline to 19.3% after treatment (p < 0.001). Improvements in BSA were consistent with an 82% reduction in the distribution of skin lesions after treatment (p < 0.05). CHM is feasible, effective, and safe for the treatment of patients with mild to moderate dermatologic events caused by EGFR inhibitors, according to our preliminary clinical experience, and has distinct advantages, including a direct approach to the TCM syndrome, diverse compatibility, and reduced anaphylactic reaction to traditional acne treatment. However, future perspectives and the need for well-designed prospective studies on CHM and EGFR inhibitors are proposed.